2015
DOI: 10.1292/jvms.15-0245
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 suppresses nuclear factor κB induced transactivation and pro-inflammatory cytokine expression in cat fibroblast cells

Abstract: Nuclear factor κB (NF-κB) is a key factor in the development of chronic inflammation and is deeply involved in age-related and metabolic diseases development. These diseases have become a serious problem in cats. Sirtuin 1 (SIRT1) is associated with aging and metabolism through maintaining inflammation via NF-κB. In addition, fibroblasts are considered an important factor in the development of chronic inflammation. Therefore, we aimed to examine the effect of cat SIRT1 (cSIRT1) on NF-κB in cat fibroblast cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Sirtuin 1 (SIRT1), a class III histone/protein deacetylase, is associated with aging and metabolism through maintaining inflammation via NF-kB. The upregulation of NF-kB transcriptional activity and pro-inflammatory cytokine mRNA expression by p65 subunit of NF-kB and lipopolysaccharide were suppressed by SIRT1 [21]. Because of the central role of NF-kB in cytokine-mediated pancreatic β-cell damage, it was postulated that SIRT1 might work in pancreatic β-cell damage models [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1), a class III histone/protein deacetylase, is associated with aging and metabolism through maintaining inflammation via NF-kB. The upregulation of NF-kB transcriptional activity and pro-inflammatory cytokine mRNA expression by p65 subunit of NF-kB and lipopolysaccharide were suppressed by SIRT1 [21]. Because of the central role of NF-kB in cytokine-mediated pancreatic β-cell damage, it was postulated that SIRT1 might work in pancreatic β-cell damage models [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth nothing that Sirt1 was recently reported that playing critical role to preventing autoimmunity and participate in sepsis progress 55 , 56 . Sirt 1 is a nicotinamide adenine dinucleotide (NAD+) dependent class III histone deacetylase (HDAC) that targets nuclear factor kappa B (NF-kB), a critical transcription factor in the regulation of proinflammatory cytokine production to adapt gene expression to metabolic activity 57 59 . Moreover, SIRT1 could regulated immunometabolic polarity during the hyper-inflammatory and hypoinflammatory phases of sepsis 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were carried out with Perfect Real Time TYBR Premix Ex Taq II (Takara, Tokyo, Japan) on an ABI 7300 Real Time PCR Sequence Detection System (Applied Biosystems, Foster City, CA) and the following shuttle PCR protocol: 95°C for 30 s, followed by 40 cycles of 95°C for 5 s, and 60°C for 35 s, in 20 μL reaction volumes containing 2 μL template cDNA, 0.8 μL primers (final concentration: 0.4 μM, including 0.4 μL ROX Reference Dye), and 6.0 μL distilled water. The primers listed in Table 1 were used for sirtuin1 and β-actin mRNA quantitation ( 20 ). Following real-time PCR, the fragment was subjected to dissociation-curve analysis to avoid nonspecific PCR amplification.…”
Section: Methodsmentioning
confidence: 99%